Gender-specific effects of short sprint interval training on aerobic and anaerobic capacities in basketball players: A randomized controlled trial - Fang, K.; Jiang, H. (Journal of Sports Science & Medicine, 2023)
This study compared the effects of a 6-week short sprint interval training (sSIT) on male and female basketball players' bio-motor abilities, aerobic fitness, and anaerobic power. Using a randomized controlled trial design, 40 basketball players of similar training backgrounds were randomly assigned to two training groups of females (n = 10) and males (n = 10) or two control groups of females and males (each of 10). The training groups performed 3 sets of 10 × 5-second all-out interval running, with a 1:3 work-to-recovery ratio, and a 3-minute rest between sets. The players were evaluated for bio-motor abilities, including muscular power assessed through the vertical jump, agility measured using a T-test and Illinois change of direction (COD) test, and maximal sprint speed measured by a 20-meter sprint test. Also, aerobic fitness was assessed by evaluating maximum oxygen consumption (V?O2max) through the Yo-Yo intermittent recovery test level 1 (Yo-Yo IR 1) test before and after the 6-week training period. After the intervention, both training groups (females and males) demonstrated significant improvements in vertical jump (effect size [ES] = 1.29, 1.06, respectively), peak power output (ES = 1.27, 1.39), T-test (ES = -0.56, -0.58), Illinois COD test (ES = -0.88, -1.1), 20-m sprint (ES = -1.09, -0.55), Yo-Yo IR1 performance (ES = 2.18, 2.20), and V?O2max (ES = 2.28, 1.75). Gender did not exhibit any significant impact on the extent of changes observed over time. The results of this study suggest that adaptations in aerobic fitness and bio-motor abilities measured in this experiment in response to sSIT are similar across genders, and gender differences should not be a major concern when implementing sSIT in basketball players.